Leadership, Discipline, and Motivation on Job Satisfaction and Teacher Performance at Public Elementary School, Bangko District, Rokan Hilir Regency - Putri, Ermanila; Rahman, Sarli; Komardi, Dadi; Momin, Mujtaba M. (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This study aims to determine and analyze the influence of leadership, discipline, and motivation on job satisfaction and teacher performance at the Bangko District Elementary School. The number of samples in this study was the entire population of the study as many as 71 civil servant teachers at the Bangko District Elementary School. Data analysis using Structural Equation Modeling (SEM) using SmartPLS 3.0 application. The results of this study indicate that leadership has a significant positive effect on job satisfaction, discipline has a significant negative effect on job satisfaction, work motivation has no significant effect on job satisfaction, leadership has no significant effect on teacher performance, discipline has a positive and insignificant effect on teacher performance, work motivation does not have a significant effect on teacher performance, organizational commitment does not have a significant effect on teacher performance and job satisfaction does not have a significant negative effect on teacher performance.